Tempe Made from Green Beans (Vigna radiata L.) and Red Beans (Phaseolus vulgaris L.) as Functional Food - Hisyam, Dhaffi Muhammad; Kurniasih, Nunung (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2024)
Tempeh is a traditional Indonesian fermented food that is rich in protein and has various health benefits. This study aims to compare the nutritional content, bioactive compounds, and antioxidant activity in tempeh made from green beans (Vigna radiata L.) and red beans (Phaseolus vulgaris L.) as functional food. Tempeh is made by fermenting green beans and red beans using Rhizopus oligosporus inoculum. The levels of proteins, fats, carbohydrates, isoflavones, antioxidant activity and water were determined. The content of bioactive compounds such as isoflavones, total phenolic, and flavonoids was measured using the HPLC method. Antioxidant activity was measured by the DPPH method. The results showed that green bean tempeh has higher levels of antioxidants and carbohydrates compared to red bean tempeh. Red bean tempeh has higher levels of fat, protein, isoflavones and water. The content of isoflavones in green bean tempeh is much lower than that of red bean tempeh. The antioxidant activity of green bean tempeh is much higher than that of red bean tempeh.